Should health services be centralized and free in pandemics? The case of Turkey as an example - Mehmet Selim Comez; Hilmi Demirkiran; Ilhan Bahar (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
The scientific board published the prevention and treatment guidelines for COVID-19 in January before the emergence of COVID-19 cases in Turkey. The constantly updated guidelines address all disease stages from the first diagnosis to the intensive care processes in detail. Furthermore, a list of reference hospitals across the country is provided in the guideline. In February, MoH stopped flights to China firstly. Then, MoH banned outbound flights to countries that reporting COVID-19 cases . The Minister of Education announced that schools were closed. It was announced on March 9th, 2020 that the first patient was diagnosed with COVID-19 in Turkey . At the beginning of May, the president announced that controlled social life would begin and that closed facilities and stopped activities would be allowed to start again in a controlled manner. The Turkish government took the necessary precautions early and swiftly. The main payer health care expenditures in Turkey is the social security institution (SSI), and also the SSI belongs to the state. The Turkish health system has already been ready for extraordinary health conditions such as this pandemic.